Corporate social responsibility and the effectiveness of local governance practices in the construction sector in Vietnam: an empirical survey-based analysis - Tran Thi Hai Yen (Otoritas : Jurnal Ilmu Pemerintahan, 2026)
Corporate Social Responsibility (CSR) is increasingly recognized as a strategic instrument for strengthening public governance and advancing sustainable development, particularly in emerging economies such as Vietnam. In the construction sector, which is characterized by high environmental and social risks, the integration of CSR remains largely voluntary, with limited regulatory enforcement and weak monitoring systems. This institutional gap creates urgency to investigate how CSR contributes to local governance effectiveness, especially within the context of ongoing digital transformation. This study examines the impact of CSR dimensions on local governance effectiveness in Vietnam’s construction sector using 110 survey based observations from firms, government officials, and experts collected between 2022 and 2024. A quantitative approach was applied, including Cronbach’s Alpha, Pearson correlation, and multiple linear regression using SPSS 26.0. The results indicate that all CSR components significantly enhance governance effectiveness, with legal and ethical responsibilities exerting a stronger influence than economic and philanthropic dimensions.   The novelty of this research lies in positioning CSR as a complementary governance mechanism rather than merely a corporate obligation. The study contributes empirical evidence to the limited literature on CSR and public governance in developing contexts and offers policy relevant insights to strengthen legal frameworks, improve multi stakeholder coordination, and promote ethical business practices for sustainable governance outcomes.